Bipolar symptoms, somatic burden, and functioning in older‐age bipolar disorder: Analyses from the Global Aging & Geriatric Experiments in Bipolar Disorder Database project. (12th August 2021) - Sajatovic, Martha; Dols, Annemiek; Rej, Soham; Almeida, Osvaldo P.; Beunders, Alexandra J.M.; Blumberg, Hilary P.; Briggs, Farren B. S.; Forester, Brent P.; Patrick, Regan E.; Forlenza, Orestes V.; Gildengers, Ariel; Jimenez, Esther; et al.
Abstract: Objective: Literature on older‐age bipolar disorder (OABD) is limited. This first‐ever analysis of the Global Aging & Geriatric Experiments in Bipolar Disorder Database (GAGE‐BD) investigated associations among age, BD symptoms, comorbidity, and functioning. Methods: This analysis used harmonized, baseline, cross‐sectional data from 19 international studies (N = 1377). Standardized measures included the Young Mania Rating Scale (YMRS), Hamilton Depression Rating Scale (HAM‐D), Montgomery‐Asberg Depression Rating Scale (MADRS), and Global Assessment of Functioning (GAF). Results: Mean sample age was 60.8 years (standard deviation [SD] 12.2 years), 55% female, 72% BD I. Mood symptom severity was low: mean total YMRS score of 4.3 (SD 5.4) and moderate‐to‐severe depression in only 22%. Controlled for sample effects, both manic and depressive symptom severity appeared lower among older individuals ( p 's < 0.0001). The negative relationship between older age and symptom severity was similar across sexes, but was stronger among those with lower education levels. GAF was mildly impaired (mean =62.0, SD = 13.3) and somatic burden was high (mean =2.42, SD = 1.97). Comorbidity burden was not associated with GAF. However, higher depressive ( p < 0.0001) and manic ( p < 0.0001) symptoms were associated with lower GAF, most strongly among older individuals. Conclusions: Findings suggest an attenuation of BD symptoms in OABD, despite extensive somatic burden. Depressive symptom severity was strongly associated with worse functioning in older individuals, underscoring the need for effective treatments of BD depression in older people. This international collaboration lays a path for the development of a better understanding of aging in BD.